Overexpression of DeltaFosB in nucleus accumbens mimics the protective addiction phenotype, but not the protective depression phenotype of environmental enrichment - Zhang, Yafang; Crofton, Elizabeth J.; Li, Dingge; Lobo, Mary Kay; Fan, Xiuzhen; Nestler, Eric J.; Green, Thomas A. (Frontiers in Behavioral Neuroscience, 2014)
Environmental enrichment produces protective addiction and depression phenotypes in rats. ΔFosB is a transcription factor that regulates reward in the brain and is induced by psychological stress as well as drugs of abuse. However, the role played by ΔFosB in the protective phenotypes of environmental enrichment has not been well studied. Here, we demonstrate that ΔFosB is differentially regulated in rats reared in an isolated condition (IC) compared to those in an enriched condition (EC) in response to restraint stress or cocaine. Chronic stress or chronic cocaine treatment each elevates ΔFosB protein levels in the nucleus accumbens (NAc) of IC rats, but not of EC rats due to an already elevated basal accumulation of ΔFosB seen under EC conditions. Viral-mediated overexpression of ΔFosB in the NAc shell of pair-housed rats (i.e., independent of environmental enrichment/isolation) increases operant responding for sucrose when motivated by hunger, but decreases responding in satiated animals. Moreover, ΔFosB overexpression decreases cocaine self-administration, enhances extinction of cocaine seeking, and decreases cocaine-induced reinstatement of intravenous cocaine self-administration; all behavioral findings consistent with the enrichment phenotype. In contrast, however, ΔFosB overexpression did not alter responses of pair-housed rats in several tests of anxiety- and depression-related behavior. Thus, ΔFosB in the NAc the shell mimics the protective addiction phenotype, but not the protective depression phenotype of environmental enrichment.